Eksotisme Dari Loro Blonyo - Sutriyanto Sutriyanto (Institut Seni Indonesia Surakarta, 2010)
Loro blonyo are wooden sculptures that resemble a pair of wedding using Java customary fashion, sitting cross-legged position. Often placed beside the statue of loro blonyo right and left door senthong is a room used for meditation (meditation) or pray to God Almighty Loro blonyo presence in our lives was a symbol of hope that bring prosperity fertile life. In the development of this sculpture not only be made by us ing media of wood but use ceramic media, gibsum and so forth. Even now its experience deformatif (witty) which has a function that is shifted from its original function. Whatever the media and shape loro blonyo has an element of high-value fine art. Keyword: loro blonyo, sculpture, symbol, Jawa, art